Factors for Implementation of Qanun in Aceh Education - Nur Hafni (Program Pascasarjana Universitas Ibrahimy, 2021)
The purpose of this study was to analyze the implementation of the Qanun on the implementation of Islamic values-based education and to interpret the obstacles and supports for implementation. Implementation referred to the content concept and context of Grindle's policies. The research method used a case study approach that was explanatory, with the type of research being descriptive qualitative data analysis. The research findings were: (1)—the implementation of the Qanun based on the principles of national policy. The specific policies of Aceh still guided it, and these principles were squeezed into educational goals and curricula. (2) the supporting factors for implementing the contents of the Qanun represent the interests of the target group, the types of benefits obtained, the type of change desired, and the elite actors in power. In contrast, the obstacles to implementation were the lack of adequate resource support, the absence of derivative policies, the degree of change that had not provided significant results, and the low compliance and responsiveness of implementing agencies.